2022
DOI: 10.1186/s12913-022-07747-3
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of patient and family engagement in hospital planning and improvement: qualitative interviews with patient/family advisors and hospital staff

Abstract: Background Patient engagement (PE) in hospital planning and improvement is widespread, yet we lack evidence of its impact. We aimed to identify benefits and harms that could be used to assess the impact of hospital PE. Methods We interviewed hospital-affiliated persons involved in PE activities using a qualitative descriptive approach and inductive content analysis to derive themes. We interpreted themes by mapping to an existing framework of healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Conversely, improved patient experience may reduce harm [ 42 ]. Patient engagement had beneficial effects and unintended or harmful impacts, such as overextended patient/family advisors, patient/family advisor turnover and clinician frustration if PFE slowed the pace of planning and improvement [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, improved patient experience may reduce harm [ 42 ]. Patient engagement had beneficial effects and unintended or harmful impacts, such as overextended patient/family advisors, patient/family advisor turnover and clinician frustration if PFE slowed the pace of planning and improvement [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Anderson et al (2022) confirmed the positive impacts of patient engagement, patient/family advisor and clinician/staff capacity to undertake PFE and the impacts of PFE outputs on clinician/staff function and processes, patient experience, and patient care outcomes [ 13 ]. Involving staff is one of the most challenging aspects in the promotion of a favorable environment to engage patients.…”
Section: Introductionmentioning
confidence: 99%